Contextualising health-disaster risk reduction pillars for under-resourced rural secondary schools in Limpopo Province, South Africa - Sibongile Khosa; Prof M.Mwale; Dr M.A. Mathaulula (International Journal of Education Sciences, 2026)
School communities in under-resourced rural settings face a disproportionate burden of health-related disasters, including outbreaks, water and sanitation failures, food insecurity and compound events that disrupt learning and wellbeing. Yet school based disaster risk reduction (DRR) evidence in Southern Africa is uneven with limited empirically guidance tailored to the organisational and infrastructural realities of disadvantaged schools. Drawing on the Comprehensive School Safety Framework and the World Health Organization's Health Emergency and Disaster Risk Management (Health EDRM) Framework as an analytic lens, this study developed context-specific pillars for health-disaster risk reduction (HDRR) in socio-economically disadvantaged secondary schools in Thulamela Local Municipality, Limpopo Province. A sequential exploratory mixed-methods design was guided the study. In Phase 1, semi-structured interviews, focus group discussions, observations and document review were undertaken with 33 purposively selected stakeholders. Qualitative insights informed a structured questionnaire which was administered in Phase 2 to 308 respondents across three schools and relevant district offices. Thematic network analysis and principal component analysis (varimax rotation) were used for qualitative and quantitative phases, respectively. The results yielded six interrelated pillars which encampassed (1) socio-psychological support and disaster awareness, (2) community-informed planning, (3) emergency health facilities and context-based policies, (4) safe transport and budget allocation, (5) communication and collaboration, and (6) assurance and resource provision. These pillars extend existing school safety guidance by specifying health focused capacities that are feasible within rural schooling systems with limited resources. The paper doucumented implications for education sector governance, health education coordination and locally accountable resourcing to strengthen preparedness, prevention and adaptation in disadvantaged schools.
Keywords: Health EDRM; Limpopo; child-centred DRR; disadvantaged schools; disaster governance; school safety